Grid-based assessment of comprehensive arable land consolidation potential in coastal saline regions: a case study of Dongying, China - Lin, Yaoben; Ye, Rongcheng; Hu, Tunan (Frontiers in Sustainable Food Systems, 2025)
Against the backdrop of increasing pressures on food security and arable land resources, evaluating the consolidation potential of cropland in coastal saline–alkali areas and optimizing governance strategies carry significant strategic importance. Taking Dongying City as a case study, this research employed a grid-based assessment approach to systematically identify the quantity potential, quality potential, and their integrated patterns of cropland consolidation. Furthermore, differentiated governance pathways and policy optimization directions were explored in light of regional heterogeneity. The results indicate that: (1) cropland consolidation potential exhibits pronounced spatial heterogeneity, with a general distribution pattern of higher potential in the central–northern areas and lower potential in the south, reflecting significant scale effects and externalities; (2) a decoupling exists between quantity and quality potential—while Hekou District shows the largest increase in cropland area, its productivity gains remain limited, whereas Lijin County, despite its smaller area, contributes the highest quality potential; (3) the comprehensive evaluation delineates three gradients of high, medium, and low potential zones, suggesting resource prioritization for high-potential areas, pilot projects in medium-potential areas, and ecological protection as the focus in low-potential areas; (4) saline–alkali conditions determine differentiated consolidation pathways, with Hekou District requiring priority investments in desalination and infrastructure, while Lijin, Guangrao, and Kenli should emphasize salt-tolerant varieties and integrated agronomic technologies. Overall, the findings highlight the necessity of adopting region-specific, differentiated strategies for cropland consolidation in coastal saline–alkali zones, avoiding “one-size-fits-all” approaches. Strengthened policy support, targeted large-scale investment, and localized adaptation of international experiences are essential to maximize consolidation benefits. This study not only provides scientific evidence for land consolidation planning in Dongying but also offers empirical insights for cropland management and food security strategies in China’s coastal saline–alkali regions.